INVESTIGATION ON THE EFFECTIVENESS OF NITROGEN GAS FOR SURFACE NITRIDING OF INTERNAL PIPE SURFACE EROSION - Mohamad Ismol, Mohamad Ismail (IRC, 2017)
This report presents an investigation on the effectiveness of nitrogen gas for surface nitriding of internal pipe erosion. Erosion in piping system always cause problems in oil and gas production facilities. Most of the issues happen due to difficulties in monitoring the condition of the internal condition of the pipe. The objective of this project is to investigate the usage of nitrogen gas in nitriding compare to ammonia for internal pipe surface hardness and erosion. The material selected for this project is Austenitic Stainless Steel 316L as it is one of the most common grade of material used in industry. The nitriding process using nitrogen gas formed a nitride layer to increase the surface hardness of the material. Different quality of nitride layer formed based on different setup of temperature used in this project. The temperature varies between below (400°C) and above (1200°C) sensitization temperature of the material to observe any formation of chromium carbide or nitride throughout the process and the effect on the quality of nitrided material. The analytical result from Scanning Electron Microscope (SEM), Energy-Dispersive X-ray Spectroscopy (EDX) and X-ray Fluorescence (XRF) was analyze to observe the microstructure and chemical composition changes on the material and showed no significant change except for the formation of carbides precipitate on nitride sample at 1200°C. No nitrogen element detected from EDX and XRF result. Two mechanical tests are used to test the nitrided material which are Vickers hardness test and scratch test to obtain the result of the performance of the nitride sample and shows that nitride sample at 1200°C performed better. As a conclusion, nitrogen gas is not effective to be used in gas nitriding process due to its molecular structure (triple bond) which is hard to be cracked and perform chemical reaction with other materials